Jombangan Javanese Pidgin from the Derivation Process in Jidor Sentulan Stage Literature - Darihastining, Susi; Wiyanto, Muhammad Saibani; ., Mukhzamilah; Bisma, Rahadian (Journal of Ecohumanism, 2024)
Theatrical literature has unique characteristics in the language patterns it produces. It can be explored as a strategic effort to preserve local cultural identity. The purpose of this study is to identify the derivational patterns that form a pidgin in the Javanese theatrical literature of Jidor Sentulan from Jombang. This research employs a qualitative approach, using componential analysis and cultural themes to examine the pidgin patterns found in Jidor Sentulan. The research setting is focused on dialogues using purposive sampling to highlight morphological aspects such as sound-altering reduplication and derivation. The validity used is theoretical validity through document observation of morphological aspects, focusing on sound-altering reduplication and derivation processes. The pidgin in Javanese experiences word formation through derivation, which tends to be understood by a specific group of Javanese speakers in Jombang. This derivation dominantly occurs through adjective-adverb-half.